Prevalence of Metabolic Syndrome Among Hispanics/Latinos of Diverse Background: The Hispanic Community Health Study/Study of Latinos - Heiss, Gerardo (American Diabetes Association, 2014)
OBJECTIVE: Approximately one-third of the adult U.S. population has the metabolic syndrome. Its prevalence is the highest among Hispanic adults, but variation by Hispanic/Latino background is unknown. Our objective was to quantify the prevalence of the metabolic syndrome among men and women 18–74 years of age of diverse Hispanic/Latino background. RESEARCH DESIGN AND METHODS: Two-stage area probability sample of households in four U.S. locales, yielding 16,319 adults (52% women) who self-identified as Cuban, Dominican, Mexican, Puerto Rican, Central American, or South American. The metabolic syndrome was defined according to the American Heart Association/National Heart, Lung, and Blood Institute 2009 Joint Scientific Statement. The main outcome measures were age-standardized prevalence of the metabolic syndrome per the harmonized American Heart Association/National Heart, Lung, and Blood Institute definition and its component abnormalities. RESULTS: The metabolic syndrome was present in 36% of women and 34% of men. Differences in the age-standardized prevalence were seen by age, sex, and Hispanic/Latino background. The prevalence of the metabolic syndrome among those 18–44, 45–64, and 65–74 years of age was 23%, 50%, and 62%, respectively, among women; and 25%, 43%, and 55%, respectively, among men. Among women, the metabolic syndrome prevalence ranged from 27% in South Americans to 41% in Puerto Ricans. Among men, prevalences ranged from 27% in South Americans to 35% in Cubans. In those with the metabolic syndrome, abdominal obesity was present in 96% of the women compared with 73% of the men; more men (73%) than women (62%) had hyperglycemia. CONCLUSIONS: The burden of cardiometabolic abnormalities is high in Hispanic/Latinos but varies by age, sex, and Hispanic/Latino background. Hispanics/Latinos are thus at increased, but modifiable, predicted lifetime risk of diabetes and its cardiovascular sequelae.